2006
DOI: 10.1038/sj.ijo.0803359
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in abdominal fat loss

Abstract: Objective: This study determined if the magnetic resonance imaging (MRI) protocol used alters the estimation of change in abdominal fat with weight loss in obese type 2 diabetic women. This study also examined if there is a uniform fat loss across the abdomen. Methods and procedures: Thirty-three obese postmenopausal women with type 2 diabetes (age 50-70 years, body mass index430 kg/m 2 ) had a total abdominal MRI scan pre-and post weight loss intervention. Three different MRI analysis protocols were used and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Thus, our observations imply that the change in both visceral and abdominal subcutaneous AT is uniform across the abdominal region. While this is consistent with prior findings from our laboratory , Kanaley et al observed regional differences in abdominal AT reduction in response to weight loss, reporting greater relative visceral AT loss in the L4‐L5 region compared with the L2‐L3 region . Explanations for the discrepent findings are unclear, but they may involve differences in study design and participant demographics.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, our observations imply that the change in both visceral and abdominal subcutaneous AT is uniform across the abdominal region. While this is consistent with prior findings from our laboratory , Kanaley et al observed regional differences in abdominal AT reduction in response to weight loss, reporting greater relative visceral AT loss in the L4‐L5 region compared with the L2‐L3 region . Explanations for the discrepent findings are unclear, but they may involve differences in study design and participant demographics.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our results, Kanaley et al 18 suggested that the number of MRI slices analyzed yields different results relative to the VAT distribution by MRI protocol used. This may cause misleading results when determining the amount of VAT loss that occurs with an intervention.…”
Section: Discussionsupporting
confidence: 81%
“…A few studies 8,18 have suggested that a single-slice image is less accurate and it may not be suitable for detecting VAT change in interventional studies. Our results also show that single-slice images have a weaker ability to detect VAT changes than multipleslice images and a single-slice image needs a larger sample size to determine VAT changes than multiple slices.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to CT-induced radiation and the relatively high cost of image analysis with MRI, abdominal adiposity (the VAT and abdominal subcutaneous adipose tissue (ASAT) depot)) is in general characterized using a single cross-sectional image at L2/L3 or L4-L5 level (22). A multi-slice protocol using slices covering the whole abdomen is, however, more accurate when intersubject comparisons are performed (23,24).…”
Section: Introductionmentioning
confidence: 99%